Perencanaan ruang terbuka publik layak anak di kawasan lapangan Astina Jaya, Desa Blahbatuh, Gianyar, Bali - Putra, Ngakan Putu Manda Teja; Utami, Ni Wayan Febriana; Asmiwyati, I Gusti Agung Ayu Rai (Jurnal Arsitektur Lansekap; Vol.5, No.1, April 2019, 2019)
Planning of children-friendly open spaces in Astina Jaya, Blahbatuh Village, Blahbatuh District, Gianyar Regency, Bali. The influence of the environment determines how a child can grow in public open space which is formed as a place of development. Village conditions directly affect the protection, growth, and development of talents and interests of children, so the form of child-friendly village will support creating a decent environment for children. Astina Jaya is a public open space in Blahbatuh village which facilitates their residents to activate in outdoor space. The existence of a child-friendly open space is one indicator of the form of children friendly village. The purpose of this study was to identify and analyze the constraints and potential of the site, also to create the appropriate concept of the site development. The methods used in this research were field survey method with data collection techniques through observation, documentation, interview and distribution of questionnaire, and also by conducting literature study. Furthermore, data were processed by tabulation method and qualitative descriptive analysis method which referred to the stages of planning process. The results showed that the spatial development consists of the core area, the buffer area, and the outer area. The concept of vegetation consists of the function of microclimate control, education, and physical barrier. The concept of circulation consists of primary and secondary circulation, and the concept of child play which is developed is a children friendly open space.